2020
DOI: 10.11591/ijeecs.v19.i1.pp459-465
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wind park tax incentives in Colombia by means of real options

Abstract: <p>The objective of this study is to assess tax incentives in Colombia to foster investment in wind parks. Fiscal incentives seek to diversify energy consumption with non-conventional renewable energy sources, since power is mostly generated by hydraulic force and since its price is impacted during dry seasons. The price of energy is modeled according to a regression toward the mean. This stochastic process was chosen because during droughts in Colombia there are price increases, which then return to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…First, tax refunds can boost enterprise profits, provide a secure environment for technological innovation, and incentivize enterprises to enhance their overall energy efficiency. A bulk of literature demonstrates that tax intervention policies effectively compensate for the positive externalities resulting from enterprise R&D investments, leading to Pareto improvements [18,20,23,42]. In contrast to indirect incentives such as tax reductions, direct government subsidies can also encourage enterprises to increase their R&D investments by raising marginal income following successful R&D or reducing marginal costs after failed attempts.…”
Section: Innovation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, tax refunds can boost enterprise profits, provide a secure environment for technological innovation, and incentivize enterprises to enhance their overall energy efficiency. A bulk of literature demonstrates that tax intervention policies effectively compensate for the positive externalities resulting from enterprise R&D investments, leading to Pareto improvements [18,20,23,42]. In contrast to indirect incentives such as tax reductions, direct government subsidies can also encourage enterprises to increase their R&D investments by raising marginal income following successful R&D or reducing marginal costs after failed attempts.…”
Section: Innovation Effectsmentioning
confidence: 99%
“…They observed that each euro increase in carbon taxes corresponded to a reduction of 11.58 kg of per capita annual emissions. Jiménez-Gómez and Acevedo-Prins [23] evaluated tax incentives for wind power plant investments in Colombia and noted that such measures promote investment in wind power plants while diversifying energy consumption through unconventional renewable sources. Sun, Zhan, and Du [18] compared value-added tax preferences for different types of new energy companies and empirically studied their impact on listed new energy companies using the difference-in-differences (DIDs) method.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis for wind turbines to overcome real time implementation challenges are provided in [29]. The price of wind energy is modeled as a regression model and an evaluation analysis of wind parks in Colombia is available in [30]. The evaluation of wind power for power production in Palestine to alleviate shortage of electricity is available in [31,32].…”
Section: Literature Reviewmentioning
confidence: 99%